Influence of advertising tools on foreign student retention in Universiti Teknologi Malaysia (UTM) / Sham Shela Omar and Nurul Zarith Zainal - Omar, Sham Shela; Zainal, Nurul Zarith (2014)
This research title is "Influence of Advertising Tools on Foreign Student Retention in Universiti Teknologi Malaysia (UTM)". There are only one purpose of this study which is to determine the relationship between advertising tools and customer retention. Besides that, there are involved two variables which are independent variable and dependent variable. The independent variable is consisting of five advertising tools which are internet, fair event, newspaper, television and poster. In order to completing this research, the hypothesis was been constructed and focus on the objective to determine whether there has significant relationship between those independent variable with dependent variable (customer retention). Meanwhile, there are 196 of foreign students have participated in this study as a respondents. The methodology used for this research was primary data collection. For primary data, the researcher was used the method of questionnaire to obtained and collection the data or information based on the independent variables and dependent variable. While the collection of data has completed, the researcher will continue with the analysing and interpret the result of the data. Hence, there are several method that will be used to analyze the data which are reliability analysis, frequency analysis, descriptive testing, Pearson`s Correlation Coefficient testing and Multiple Regression method. The result of the correlation testing was shows that all of the independent variable is significant and moderate relationship with the customer retention (dependent variable). Thus, for the multiple regression analysis shown that the most significant and has proven that there the factor in influence the customer retention which are television, internet and poster compared to fair event and newspaper are clearly shows that both independent variable is a weak factor toward customer retention. For the hypothesis, there are only three of hypothesis which including internet, television and poster is accepted while the fair event and newspaper is not accepted.